The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3389/fpsyg.2021.680124
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Dimensionality of Early Numeracy Using the Bifactor Exploratory Structural Equation Modeling Framework

Abstract: The few studies that have analyzed the factorial structure of early number skills have mainly used confirmatory factor analysis (CFA) and have yielded inconsistent results, since early numeracy is considered to be unidimensional, multidimensional or even underpinned by a general factor. Recently, the bifactor exploratory structural equation modeling (bifactor-ESEM)—which has been proposed as a way to overcome the shortcomings of both the CFA and the exploratory structural equation modeling (ESEM)—proved to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 92 publications
0
3
0
Order By: Relevance
“…This would be consistent with both the broad number sense factor proposed by Braeuning et al [18], and the multifactorial model proposed by Milburn et al [19] that includes a combined numeracy factor alongside distinct curriculum-aligned factors. This conceptualisation would also be consistent with suggestions that early numeracy is likely composed of both general and domain specific numerical factors [9,47]. Further research is needed both to more directly assess these hypotheses, and to assess whether or not the proposed core skills are more relevant to early numerical development than curriculum-aligned skills.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…This would be consistent with both the broad number sense factor proposed by Braeuning et al [18], and the multifactorial model proposed by Milburn et al [19] that includes a combined numeracy factor alongside distinct curriculum-aligned factors. This conceptualisation would also be consistent with suggestions that early numeracy is likely composed of both general and domain specific numerical factors [9,47]. Further research is needed both to more directly assess these hypotheses, and to assess whether or not the proposed core skills are more relevant to early numerical development than curriculum-aligned skills.…”
Section: Discussionsupporting
confidence: 75%
“…In addition to study aims and methods impacting the number of factors identified, different analysis techniques may suggest alternative ways of interpreting the structure of early numeracy. For instance, Dierendonck et al [47] investigated early numeracy using various modelling techniques, including CFA, bifactor-CFA, and bifactor exploratory structural equation modelling. A key distinction between these techniques is that bifactor models account for any shared communality of items through assuming the construct (e.g., early numeracy) is independently influenced by both a single general factor plus several domain specific factors.…”
Section: Several Recent Studies Have Assessed and Supported The Model...mentioning
confidence: 99%
“…The bootstrapping method was employed (Bootstrap = 5000), and the preliminary CFA results revealed that the four-factored model established in Study 2 was mildly supported (χ 2 = 666.36, df = 98, χ 2 /df = 6.80, CFI = 0.87, RMSEA = 0.10, SRMR = 0.09). The information obtained through the goodness-of-fit test indicated that ESEM was required to broaden our understanding of the organization of CWB ( Marsh et al, 2013 ; Fresno et al, 2020 ; Dierendonck et al, 2021 ; Gegenfurtner and Quesada-Pallarès, 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…Doing so can provide useful information for determining the latent optimal structure of CWB established in the literature ( Asparouhov and Muthén, 2009 ). CFA has been criticized for its overly simplistic, restrictive, and idealistic independent cluster model assumption ( Xiao et al, 2019 ; Dierendonck et al, 2021 ), which has led to CFA frequently failing to meet several standards of good measurement (e.g., goodness-of-fit, measurement invariance, and well-differentiated factors; Marsh et al, 2020 ). Because of this, ESEM has been proposed as a potential alternative.…”
Section: Introductionmentioning
confidence: 99%
“…Suppose we have assessed early numeracy (Dierendonck et al, 2021) with a standardized test in a sample consisting of 140 kindergarten children (the SAS listing to generate the data set and the listing for the analyses as well as the respective output are provided in Appendix B). The test encompasses three theoretical facets, each assessed by 10 items, namely counting, relations, and arithmetic.…”
Section: Specifying Irt Models With the Hbmirt Macromentioning
confidence: 99%